Eutirucallin: A Lectin with Antitumor and Antimicrobial Properties - Palharini, Julio G.; Richter, Aline C.; Silva, Mariana F.; Ferreira, Flavia B.; Pirovani, Carlos P.; Naves, Karinne S. C.; Goulart, Vivian A.; Mineo, Tiago W. P.; Silva, Marcelo J. B.; Santiago, Fernanda M. (Frontiers in Cellular and Infection Microbiology, 2017)
Eutirucallin is a lectin isolated from the latex of Euphorbia tirucalli, a plant known for its medical properties. The present study explores various characteristics of Eutirucallin including stability, cytotoxicity against tumor cells, antimicrobial and antiparasitic activities. Eutirucallin was stable from 2 to 40 days at 4oC, maintained hemagglutinating activity within a restricted range, and showed optimal activity at pH 7.0-8.0. Eutirucallin presented antiproliferative activity for HeLa, PC3, MDA-MB-231 and MCF-7 tumor cells but was not cytotoxic for non-tumorigenic cells such as macrophages and fibroblasts. Eutirucallin inhibited the Ehrlich ascites carcinoma in vivo and it was also observed that Eutirucallin inhibited 62.5% of Escherichia coli growth. Also, Eutirucallin showed to be effective when tested directly against Toxoplasma gondii infection in vitro. Therefore, this study sheds perspectives for pharmacological applications of Eutirucallin.